Focus on teaching pronunciation in teaching foreign languages.: Focus on teaching pronunciation in teaching foreign languages. - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2021)
Abstract: Teaching correct pronunciation to the students who are learning foreign languages is often neglected in English language lessons. The importance of correct pronunciation is unquestionable as it is a basic and inevitable aspect of well-understood communication. Therefore, it is necessary to be taught and practiced right from the early stage of English language teaching, because young learners are the best recipients and often can achieve flawless-like pronunciation. The article analyzes the ways of teaching pronunciation, but without particular focus on different features of pronunciation and using limited teaching techniques and materials are often ineffective.